2006
DOI: 10.1534/genetics.105.049155
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy Genes From Weedy Rice Respond Divergently to Seed Development Environments

Abstract: Genes interacting with seed developmental environments control primary dormancy. To understand how a multigenic system evolved to adapt to the changing environments in weedy rice, we evaluated genetic components of three dormancy QTL in a synchronized nondormant genetic background. Two genetically identical populations segregating for qSD1, qSD7-1, and qSD12 were grown under greenhouse and natural conditions differing in temperature, relative humidity, and light intensity during seed development. Low temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Biological characteristics can clarify typical weedy rice types and provide a theoretical basis for its prevention and control. Moreover, related species materials for gene flow studies in the environmental safety assessment of genetically modified rice, and valuable resistance genes should be explored as breeding materials (Lu and Snow, 2005;Gu et al, 2006;Rong et al, 2007). (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Biological characteristics can clarify typical weedy rice types and provide a theoretical basis for its prevention and control. Moreover, related species materials for gene flow studies in the environmental safety assessment of genetically modified rice, and valuable resistance genes should be explored as breeding materials (Lu and Snow, 2005;Gu et al, 2006;Rong et al, 2007). (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that lowering seed maturation temperatures induces high levels of dormancy in rapid cycling Arabidopsis ecotypes (Schmuths et al, 2006;Donohue et al, 2008;Chiang et al, 2009) as well as other species (Fenner, 1991;Gu et al, 2006). We confirmed that this was indeed a dormancy phenomenon by stimulating high levels of germination in seeds matured at low temperatures by applying multiple dormancy breaking treatments or by removing coat-imposed dormancy by nicking the seed coat (see Supplemental Figure 1A online) and by showing that embryo and seed coat morphology was normal in seeds developed at 108C (see Supplemental Figures 1B and 1C online).…”
Section: Identification Of Temperature-dependent Transcripts In Maturmentioning
confidence: 99%
“…Secondary dormancy remains an important characteristic in indica varieties, where seeds retain viability during hot, humid conditions between planting seasons. The most detailed studies of dormancy have been conducted with an accession of wild-like weedy rice from Thailand (accession SS18-2) that exhibits hull-imposed dormancy [21][22][23][24][25][26]. The most important dormancy-related QTL in this Thai accession was located on chromosome 12, explaining about 50% of the phenotypic variance [22,24].…”
Section: Dormancymentioning
confidence: 99%